THE CONCEPT, EVOLUTION AND CHALLENGES OF DIGITAL LIBRARY DEVELOPMENT IN NIGERIA - Sadiku, Shaibu Adona (Sokoto Educational Review, 2015)
The adoption of information and communication technologies in information environment has made a radical change in information management. One of such revolutions has exhibited in the form of digital libraries. The evolution of digital libraries has ensured the emergence of global networked environment that has dramatically changed the status of libraries, their processes, service delivery as well as storage and retrieval systems. This paper examines the development of digital libraries, the concept, characteristics, funding, infrastructure, and ICT policy in Nigeria. The paper enumerates a number of challenges hindering the development of digital libraries in Nigeria and proffers some recommendations.